The fourth SNRU international conference on coopertion for development on the East - West economic corridor: Human resouce development for entering Asean community - Chandokham Yowya bouth; Nguyễn Đức Vượng, Hoàng Dương Hùng (Trường Đại học sakon nakhon rajabhat, 2011)
vv